Nurses’ Performance Regarding Care of Patients Undergone Liver Transplantation: A Comparative Cross-Sectional Study: Nurses’ Performance Towards Liver Transplantation Patients - Imtiaz , Sehrish; Yaqoob, Adnan; Khan, Sadia (Pakistan Journal of Health Sciences, 2022)
Viral hepatitis is the seventh largest cause of mortality, with the hepatitis C virus accounting for over half of all viral hepatitis deaths. The nurse plays a vital role in any team of health care professionals concerned within the care of patients. To determine the nurses’ performance regarding care of patients undergone liver transplant. Methods: A comparative cross-sectional study was conducted at Liver transplant surgery unit, Pakistan Kidney and Liver institute and research center and Bahria International hospital Lahore. Total 86 nurses were enrolled. Data were collected on a predesigned nurse’s performance questionnaire regarding post liver transplant care and socio demographic characteristics for nurses including age, gender, qualification, duty shift and work experience were noted. Statistical analysis was performed by using the Statistical Package for Social Sciences (SPSS) version 24.0. The frequencies, percentages were calculated for qualitative variables and Mean + SD were calculated for quantitative variables. Results: The mean age of nurses in group A as 29.32+5.62 and in group B as 29.35+5.45. Out of 43 participants 9(20.9%) were males whereas 34(79.1%) were females in group A and in group B there were 14(32.6%) were males and 29(67.4%) were females. The mean ranks in group A was 22.66 and in group B it was observed as 21.31. Insignificant difference has been observed in both groups (p-value 0.720). Conclusion: In this study, it was concluded that the performance of nurses in terms of patient care is insufficient after liver transplantation